OP0157 Apoptosis resistance of synovial fibroblasts of patients with rheumatoid arthritis is regulated by the long non-coding rna fas-as1. (15th June 2017) - Pajak, A; Horai, Y; Pachera, E; Brock, M; Gay, S; Neidhart, M; Distler, O; Jungel, A; ,
Abstract : Background: Apoptosis resistance is thought to contribute to the accumulation of synoviocytes in the affected joints of patients with rheumatoid arthritis (RA). Of particular interest, the Fas receptor (FasR) - Fas ligand (FasL) apoptotic pathway appears altered in RA 1 . Long non-coding RNAs (lncRNAs) are emerging as key regulators of gene expression. Their role in disease, however, is still poorly understood. The recently described lncRNA FAS-AS1 has been implicated in alternative splicing of FasR. This results in increased amounts of soluble FasR (sFasR) and thereby prevents FasL-induced cell death 2, 3 . Whether lncRNA FAS-AS1 is involved in the apoptosis resistance of synovial fibroblasts in RA is unknown. Objectives: To assess the regulatory role of lncRNA FAS-AS1 in the apoptosis resistance of synovial fibroblasts from patients with RA (RASF). Methods: Levels of expression of lncRNA FAS-AS1 were measured in RASF and synovial fibroblasts from patients with osteoarthritis (OASF) by qPCR using SYBRGreen detection. Cells were treated with TNFα (10ng/ml, 24h) and/or with FasL (50ng/ml, 18h) to assess the secreted amount of sFasR by ELISA and the induction of apoptosis by Annexin V staining followed by flow cytometry. LncRNA FAS-AS1 was silenced using locked nucleic acid antisense oligonucleotides (GapmeR). Results: There was no significant difference in basal levels of lncRNA FAS-AS1 expression between RASF and OASF (n=4 each). TNFα stimulation of synovial fibroblasts, regardless of the disease context (RA or OA), resulted in higher than 6-fold induction of lncRNA FAS-AS1 expression (6.45±1.39; p<0, 05; n=4 for RASF and 6.26±1.47; p=0.05; n=4 for OASF). In addition, TNFα stimulation induced secretion of sFasR in RASF from 107±74 to 390±274pg/ml (p<0.05; n=6) and OASF from 69±54 to 249±134pg/ml (p<0.05; n=6). FasL induced apoptosis in both RASF and OASF (55–75±13%). However, pretreatment with TNFα reduced the FasL-induced apoptosis in RASF by 25±19% and in OASF by 15±10%. Silencing with GapmeR successfully decreased the expression of lncRNA FAS-AS1 by 40±22% SEM. Most interestingly, silencing of lncRNA FAS-AS1 reverted the TNFα inhibitory effect on FasL-induced apoptosis by 37±11% (n=4). Conclusions: Our data revealed a novel mechanism, which may underlie apoptosis resistance in RASF. We showed that in a pro-inflammatory cytokine milieu, lncRNA FAS-AS1 up-regulates the release of sFasR and thereby may lower the responsiveness of cells to death signals. Thus, targeting lncRNA FAS-AS1 might prevent apoptosis resistance and synovial hyperplasia in RA. References: Hong et al., Life Sciences. 2015; Feb 1; 122:37–41. Seghal et al., Leukemia. 2014; Dec 28(12); 2376–87. Villamizar et al., Oncotarget. 2016; Mar 22; 7(12):13810–26. Disclosure of Interest: A. Pajak: None declared, Y. Horai: None declared, E. Pachera: None declared, M. Brock: None declared, S. Gay Grant/research support from: EU project BTCure, IAR, Consultant for: GSK, M. Neidhart Grant/research support from: Baugartenstiftung, O. Distler Grant/research support from: Actelion, Bayer, Boehringer Ingelheim, Pfizer, Sanofi, Consultant for: 4 D Science, Actelion, Active Biotec, Bayer, BiogenIdec, BMS, Boehringer Ingelheim, ChemomAb, EpiPharm, espeRare foundation, Genentech/Roche, GSK, Inventiva, Lilly, medac, Mepha, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Pfizer, Sanofi, Serodapharm, Sinoxa, Speakers bureau: AbbVie, iQone Healthcare, Mepha, A. Jungel: None declared